Micro-fibrous structured catalysts vs conventional catalytic systems: direct comparison of the mass transfer efficiency - Lopatin S.; Mikenin P.; Zazhigalov S.; Pisarev D.; Baranov D.; Zagoruiko A. N. Andrey Nikolaevich (2016, 2016)
Title screen